Evaluation of Nutrient Composition and Biostimulant Properties of Seaweeds for Improving Soil Microbial Population and Tomato Plant Growth - Venci Candida Xavier James; Arokya Glory Pushpa Thiraviam; Munirah Abdullah Al-Dosary; Ashraf Atef Hatamleh; Najat A. Bukhari; Selvaraj Arokiyaraj; Moni Kalaiyarasi (BioResources)
The nutrient composition and biostimulant properties of seaweed were determined as solid biofertilizer for cultivating tomato seedlings in a greenhouse. Seaweeds (Sargassum wightii, Sargassum longifolium, Laminaria digitata, and Gelidiella acerosa) were collected from rocky areas and turned into a powder, and their nutrient compositions were analyzed. The brown seaweed showed indoleacetic acid (IAA), gibberellic acid (GA3), indole butyric acid (IBA), and abscisic acid (ABA). The amount of IAA ranged from 0.52 to 21.5 μg/mL. Compared with the other brown algae, the G. acerosa extract presented the maximum amount of GA3 (149 μg/mL). The amount of IBA ranged from 1.5 to 15.3 μg/mL, and the ABA level was high in S. wightii (2.5 μg/mL). All algae powders were subjected to biofertilizer preparation and their biostimulant properties were studied. The algal biostimulant improved flower cluster number, fruit number, shoot dry weight, and root dry weight in tomato plants in a greenhouse. Macroalgae fertilizer improved urease, phosphatase, invertase, and catalase activities (p<0.05) and the microbial population in the soil. The results showed positive effects of biostimulants on soil physicochemical and biological properties.